Lactobacillus frumenti Facilitates Intestinal Epithelial Barrier Function Maintenance in Early-Weaned Piglets - Hu, Jun; Chen, Lingli; Zheng, Wenyong; Shi, Min; Liu, Liu; Xie, Chunlin; Wang, Xinkai; Niu, Yaorong; Hou, Qiliang; Xu, Xiaofan; Xu, Baoyang; Tang, Yimei; et al. (Frontiers in Microbiology, 2018)
Increased intestinal epithelial barrier function damages caused by early weaning stress have adverse effects on swine health and feed utilization efficiency. Probiotics have emerged as the promising antibiotic alternatives used for intestinal barrier function damage prevention. Our previous data showed that Lactobacillus frumenti was identified as a predominant Lactobacillus in the intestinal microbiota of weaned piglets. However, whether the intestinal epithelial barrier function in piglets was regulated by L. frumenti is still unclear. Here, piglets received a PBS vehicle or PBS suspension (2 ml, 108 CFU/ml) containing the L. frumenti by oral gavage once a day during the period of 6-20 days of age prior to early weaning. Our data demonstrated that oral administration of L. frumenti significantly improved the intestinal mucosal integrity and decreased the serum endotoxin and D-lactic acid levels in early-weaned piglets (26 days of age). The intestinal tight junction proteins (including ZO-1, Occludin, and Claudin-1) were significantly up-regulated by L. frumenti administration. The serum immunoglobulin G (IgG) levels, intestinal secretory immunoglobulin A (sIgA) levels, and interferon-γ (IFN-γ) were significantly increased by L. frumenti administration. Furthermore, our data revealed that oral administration of L. frumenti significantly increased the relative abundances of health-promoting microbes (including L. frumenti, Lactobacillus gasseri LA39, Parabacteroides distasonis, and Kazachstania telluris) and decreased the relative abundances of opportunistic pathogens (including Desulfovibrio desulfuricans and Candida humilis). Functional alteration of the intestinal bacterial community by L. frumenti administration was characterized by the significantly increased fatty acids and protein metabolism and decreased diseases-associated metabolic pathways. These findings suggest that L. frumenti facilitates intestinal epithelial barrier function maintenance in early-weaned piglets and may be a promising antibiotic alternative used for intestinal epithelial barrier function damage prevention in mammals.